Distribution of Porphyromonas gingivalis fimA and mfa1 fimbrial genotypes in subgingival plaques - Nagano,Keiji; Hasegawa,Yoshiaki; Iijima,Yura; Kikuchi,Takeshi; Mitani,Akio (PeerJ, 2018)
Background Strains of periodontal disease-associated bacterium Porphyromonas gingivalis have different pathogenicity, which can be attributed to clonal genetic diversity. P. gingivalis typically expresses two types of fimbriae, FimA and Mfa1, which comprise six (I, Ib, II, III, IV, and V) and two (mfa53 and mfa70) genotypes, respectively. This study was conducted to investigate the distribution of the two fimbrial genotypes of P. gingivalis in clinical specimens. Methods Subgingival plaques were collected from 100 participants during periodontal maintenance therapy and examined for P. gingivalis fimbrial genotypes by direct polymerase chain reaction and/or DNA sequencing. We also analyzed the relationship between fimbrial genotypes and clinical parameters of periodontitis recorded at the first medical examination. Results Both fimbrial types could be detected in 63 out of 100 samples; among them, fimA genotype II was found in 33 samples (52.4%), in which the mfa70 genotype was 1.75 times more prevalent than mfa53. The total detection rate of fimA genotypes I and Ib was 38.1%; in these samples, the two mfa1 genotypes were observed at a comparable frequency. In two samples positive for fimA III (3.2%), only mfa53 was detected, whereas in four samples positive for fimA IV (6.3%), the two mfa1 genotypes were equally represented, and none of fimA V-positive samples defined the mfa1 genotype. No associations were found between clinical parameters and fimbrial subtype combinations. Discussion Both P. gingivalis fimbrial types were detected at various ratios in subgingival plaques, and a tendency for fimA and mfa1 genotype combinations was observed. However, there was no association between P. gingivalis fimbrial genotypes and periodontitis severity.
Keywords: Fimbriae; Porphyromonas gingivalis; FimA; Genotype; Periodontitis; Mfa1